OPTIMASI KONSENTRASI ASAM SULFAT DAN KECEPATAN PENGADUKAN PADA PROSES HIDROLISIS AMPAS TEBU MENJADI FURFURAL - Andaka, Ganjar (Lembaga Penelitian & Pengabdian Kepada Masyarakat (LPPM), IST AKPRIND Yogyakarta, 2013)
ABSTRACT Hydrolysis of bagasse in the presence of sulfuric acid catalyst to produce furfural was studied. This objective of this work was to study the effects of catalyst consentration and stirrer speed on yield of furfural. The experiment were conducted by reacting bagas-se with sulfuric acid in a three neck flask sized 500 mL equipped with stirrer, heater, condenser, and thermometer. The reaction condition studied were catalyst concentration ranging from 4% to 20% and stirrer speed from 100 rpm to 500 rpm at reaction temperature 100ÂºC and reaction time 120 minutes. The concentration of furfural was analyzed to calculate the yield of furfural. The analysis of bagasse obtained that the water content of 6.76% and pentosan content of 18.86%. The results show that yield of furfural reached a maximum at the catalyst concentration of 8% is 5.79% and the yield of furfural reached an optimum at the stirrer speed of 400 rpm is 6.29%.